ISLAMIC EDUCATION AND ISLAMIC COMMUNICATION GUIDANCE MODEL IMPLEMENTATION IN COMPETENCY DEVELOPMENT PNS IN THE NORTH SUMATRA PROVINCE - Ahmad Fauzi Batubara; Syukur Kholil; Rubino Rubino (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The implementation of an agency's work obligations depends in large part on communication. The application of Islamic communication is thought to be capable of aiding in the development of a positive communication environment with Islamic ideals. The BPSDM of North Sumatra Province did not implement qaulan sadida in the best possible way at the Regional Apparatus Forum. The compilation of work plans becomes tedious from year to year and is often unresponsive to pressing difficulties since the information and data provided, both from message elements and feedback elements, are frequently inaccurate. Living modestly and without excess is a component of Qaulan Maysura that has been put into practice. Islamic advice and communication have a significant part in fostering a collaborative work environment. This serves as the framework for a method that can foresee every issue that can arise during the coordination process and handle it through to the point of accountability for the work done.